Effect of Renin-Angiotensin System Inhibitors on Acute Kidney Injury Among Patients Undergoing Cardiac Surgery: A Review and Meta-Analysis - Zhou, Han (ELSEVIER INC, 2022)
10.1053/j.semtcvs.2020.11.024